109 Defining the Effectiveness of Lumbar Spine Surgery in a Nationwide, Prospective Longitudinal Quality of Life Registry: An Analysis of Variability in Patient-Reported Outcomes and Preliminary Predictive Models of Treatment Failure. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Godil, Saniya S.; McGirt, Matthew J.; Glassman, Steven D.; Knightly, John J.; Mummaneni, Praveen V.; Oetting, Gregory; Theodore, Nicholas; Gottfried, Oren N.; Khairi, Saad; Schmidt, Meic H.; Boakye, Maxwell; Kalkanis, Steven N.; et al.
Abstract: INTRODUCTION: Thirty percent of US healthcare expenditures support care that is ineffective in real-world (non-research) settings. Efficacious treatments in research settings often fail to prove effective at the individual-patient level when applied in everyday-care settings. Prospective patient-reported-outcome (PRO) registries measuring this wide spectrum of care may allow for identification of optimized care paradigms, refine surgical delivery, and demonstrate the value of spine surgery. METHODS: A nationwide, web-based, prospective, longitudinal 1-year outcomes registry was introduced into 49 spine practices. Using standardized process of representative sampling, baseline, perioperative, 3- and 12-month medical record and PRO was entered prospectively for 5 surgical spine diagnoses. RESULTS: To date, 37 sites with 236 surgeons from 29 US states have enrolled 7951 patients [2743 (34.8%) disc herniation, 2678 (34.0%) stenosis, 1549 (19.6%) spondylolisthesis, 487 (6.2%) recurrent-disc herniation, 426 (5.4%) adjacent segment disease] Table 1. Of 7951 patients enrolled, 4970 have passed 3-month follow-up with an 81% follow-up rate and 1822 have passed 12-month follow-up with a 74% follow-up rate. Mean pain (VAS-LP:6.9 vs 2.6, VAS-BP: 6.5 vs 3.3), disability (Oswestry Disability Index [ODI]: 49.8 vs 25.3), and quality-of-life (EuroQOL 5 dimensions questionnaire [EQ-5D]: 0.54 vs 0.76) were improved at 12-months postoperatively ( P < .001) (Figure 1A). However, 194 (11%) patients reported no improvement in ODI (ranging 8-17% per diagnosis) and 536 (29.4%) failed to achieve a minimum-clinical-important-difference (MCID) level of improvement in ODI (range: 24%-48% per diagnosis) (Figure 1B). Only 65% of patients reported outcome met expectations, and 12% would not undergo surgery again. Lack of college degree, smoking, depression, back dominant symptoms, a prior spine surgery, workers comp or liability/disability claim, and symptom duration >3 months were associated with failure to achieve MCID 12 months after lumbar surgery. Patients with 2 (odds ratio [OR]: 1.2), 3 to 4 (OR: 2.1) or 5 (OR: 2.9) of these preoperative characteristics had increasing odds of treatment failure (Figure 2, Table 2). CONCLUSION: Lumbar surgery was effective at improving pain, disability, and quality-of-life for 5 common lumbar diagnoses. Significant variability exists in effectiveness of surgical care at individual-patient level, and many patients experience little to no benefit from surgery in current real-world practice paradigms. Individual patient profiles may identify patients least likely to improve.